Cognitive predictors of adolescent social anxiety - Chiu, K; Clark, DM; Leigh, E (Elsevier, 2020)
Background Identifying psychological processes that maintain social anxiety holds promise for improving treatment outcomes for young people. Experimental and prospective studies in adults suggest negative social cognitions, safety behaviours, self-focused attention, and pre- and post-event processing are all implicated in the maintenance of social anxiety. Despite social anxiety typically starting in adolescence, prospective studies examining these cognitive processes in youth are lacking. The current study examined prospective associations between these five cognitive processes and social anxiety in a sample of 614 participants (53% girls; aged 11–14 years). Methods Psychological processes, social anxiety symptoms, and depressive symptoms were assessed using self-report questionnaires at two time points.